2000
DOI: 10.1023/a:1005583117296
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stability and Catalytic Efficiency of Yeast Hexokinase Upon Interaction with Zwitterionic Micelles. Kinetics and Conformational Studies

Abstract: The effect of ligands (glucose, ATP and Mg2+) and zwitterionic micelles of lysophosphatidylcholine (LPC) or N-hexadecyl-N,N-dimethyl-3-ammonium propanesulfonate (HPS) in the yeast hexokinase (HK) stability was studied at 35 degrees C. The thermal inactivation kinetics followed one-exponential decay. The effect of ligands on protecting the enzyme against inactivation followed the order: glucose > glucose/Mg2+ >ATP/Mg2+ approximately or approximately equal to Mg2+l approximately or approximately equal to buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Therefore, the observed effects depend on the type of interaction, which can be modulated by changes in pH or ionic strength. These studies with different enzymes showed a correlation between the changes in the kinetic and some conformational property of these proteins as studied by fluorescence [17][18][19], UVdifference [17] or ESR [16] spectroscopy.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, the observed effects depend on the type of interaction, which can be modulated by changes in pH or ionic strength. These studies with different enzymes showed a correlation between the changes in the kinetic and some conformational property of these proteins as studied by fluorescence [17][18][19], UVdifference [17] or ESR [16] spectroscopy.…”
Section: Introductionmentioning
confidence: 92%
“…The activity and stability of soluble enzymes in aqueous micelles is closely related to the chemical nature of the surfactant [16][17][18][19][20]. Therefore, the observed effects depend on the type of interaction, which can be modulated by changes in pH or ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in head group size or hydrophilicity of surfactant play a significant role on the superactivity of α‐CT and hydrophobic chain promotes additives–enzyme interactions. The influence of additives on the catalytic properties of enzymes strongly depends on the additive structure, that is, the charge and the size of the head group and on the nature of the substrate 19–23. Alfani and coworkers 24–27 reported a positive correlation between the superactivity of α‐CT and the surfactant hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Hexokinases catalyse the transfer of a phosphoryl group from ATP to hexoses, where the reaction is usually studied by a coupled enzyme assay with glucose-6-phosphate dehydrogenase. 20 Since hexokinases use two substrates, glucose and ATP, in the reaction, it is essential to use limited amounts of one substrate, maintaining the other in excess in order to find Q T and, consequently, DH cal . This is necessary since one of the substrates should be totally consumed to obtain DH cal .…”
Section: Itc Of Enzyme Catalysed Reactionsmentioning
confidence: 99%
“…It is also possible to use a coupled enzyme assay in order to study one particular reaction in which the product can be used as a reactant by an additional enzyme. 20,21 The disadvantage of this method is the need for large amounts of the additional enzyme and the required cofactors to avoid unintended errors in the characterization of the enzyme of interest.…”
mentioning
confidence: 99%